The contribution of domestic and family violence death reviews in Australia: From recommendations to reform? - Buxton-Namisnyk, Emma (Journal of criminology, 2024)
A key aim of domestic violence death reviews (DVDRs) is to recommend improvements to domestic violence service responses, thereby preventing future domestic violence-related deaths. However, there is little scholarship examining the implementation of DVDR recommendations. This study analyses all recommendations made by two Australian DVDR bodies, from the time of each body's establishment until September 2023, alongside government responses and implementation information. Our findings show that despite high levels of initial government acceptance of DVDR recommendations there remains a considerable implementation gap. We consider implementation barriers, suggest improvements to recommendation monitoring and identify areas for future research.